Pengaruh Net Generation Terhadap Interaksi Sosial Pada Pelajar Sma Negeri I Kota Sukabumi - Marnoto; Ajeng Trijayanti (Jurnalika : Jurnal Ilmu Komunikasi, 2023)
Indication of the problem from this research is social interaction that cannot be separated from the communication process. Social interaction in the real world is reduced due to the presence of advanced technology, informational society and the Internet generation or the Net Generation. This generation tends to interact in cyberspace, so social interaction in real life is increasingly limited. From this background, the research aims to determine Net Generation among students of SMAN I Sukabumi City, social interaction of Net Generation, and how much influence Net Generation has on social interaction. This study uses an associative descriptive method with Rating Scale measurements and analysis using a continuum line. Meanwhile, to find out how big the correlation between the two variables, the researcher used the product moment correlation formula, the coefficient of determination and hypothesis testing. Meanwhile, for processing the data results, the application of Statistical Product and System Solution (SPSS) Statistics Version 14.0 is used. The sample in this study was 115 people from a total population of 1,720 people. The sampling technique used was random sampling. Based on the results of the analysis, the Net Generation of SMAN I students in Sukabumi City obtained an average value of 3.8 and was in the agree category. Social interaction in SMAN I Sukabumi students obtained an average score of 3.7 and entered the agree category. There is a positive and significant influence between Net Generation and Social Interaction. This is based on the results of the calculation of the Pearson product moment coefficient, the correlation value (837) is 0.837, which means that there is a very strong correlation. The coefficient of determination is 70% while the remaining 30% is the influence of other variables that are not included in the research title. Then to test the hypothesis, because t count > t table which is 16.47 > 1.981 then Hₒ is rejected. In conclusion, there is a positive and significant influence between Net Generation on Social Interaction in Students of SMAN I Sukabumi City.